\documentclass[10pt,a4paper]{article}
\usepackage[latin1]{inputenc}
\usepackage{amsmath}
\usepackage{amsfonts}
\usepackage{amssymb}
\usepackage{graphicx}
\begin{document}
The first implication we assume abelian and show homomorphism
\(\phi(x,y),(x_{1},y_{1}) =\phi(xx_{1},yy_{1})=xx_{1}yy_{1}=xyx_{1}y_{1}=\phi(x,y)\phi(x_{1},y_{1})\)
The second implication we assume homomorphism and show that \(G\) is abelian
\(\phi(x,y),(x_{1}y_{1})=\phi(x,y)\phi(x_{1}y_{1})=xyx_{1}y_{1}\)
\(\phi(x,y),(x_{1}y_{1})=\phi(xx_{1},yy_{1}) = xx_{1}yy_{1}